2015
DOI: 10.1016/j.ausmj.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening Social Marketing Research: Harnessing “Insight” through Ethnography

Abstract: This paper aims to challenge social marketers to extend their research repertoire beyond restrictive 'individualised rationalities' driving reliance on scientifically proven evidence, population data and focus groups as insight-oriented research. Social marketing, as a discipline, is constrained by using techniques aimed at (dis)proving scientific hypotheses, thus misses the mark when it comes to creating effective social change. Gaining insight into human conduct requires research tools that examine the deep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 71 publications
(79 reference statements)
1
24
0
2
Order By: Relevance
“…Using the principles of digital ethnography [21], online conversations involve the use of a powerful online insights community methodology (taking place in specifically-created virtual lounge rooms) and are used globally by major companies and health agencies to obtain insights into consumer behaviour [22]. Online conversations generate rich insights that go beyond the capabilities of traditional research approaches, as participants in the online communities' converse over a longer period of time responding to questioning from group moderators.…”
Section: Methodsmentioning
confidence: 99%
“…Using the principles of digital ethnography [21], online conversations involve the use of a powerful online insights community methodology (taking place in specifically-created virtual lounge rooms) and are used globally by major companies and health agencies to obtain insights into consumer behaviour [22]. Online conversations generate rich insights that go beyond the capabilities of traditional research approaches, as participants in the online communities' converse over a longer period of time responding to questioning from group moderators.…”
Section: Methodsmentioning
confidence: 99%
“…One method to help researchers gather culturally relevant insights (Brennan et al, 2015; Weidner et al, 2010) and provide a deep understanding of the lives of citizens (Nailer et al, 2015) is ethnography, which remains largely underutilized in social marketing (Brennan et al (2015). Nailer et al (2015) and Belk (2014) identified the value of qualitative and ethnographic research in LMICs, noting the limitations of quantitative research for gaining deep understanding of context-sensitive issues.…”
Section: Methodsmentioning
confidence: 99%
“…A pesar que el propósito de Andreasen evolucionó en Europa y Estados Unidos, los cambios de comportamiento seguían siendo dirigidos hacia el individuo, desconociendo que los comportamientos son el resultado de interacciones con otras personas que cumplen otros roles o sencillamente facilitan la ocasión no deseada (Brennan et al, 2015) Kotler y Roberto (1989) propusieron un esquema basado en la tangibilidad del producto de MS, porque algunas causas son menos tangibles que otras por requerir el uso de elementos para lograr resultados y requieren un enfoque más multifacético. La clasificación empleada recientemente es el más difundido como es el MS de buenas causas, el MS Corporativo para promover acciones de cambio de comportamiento en busca de mejorar la calidad de vida de las comunidades y el MS de Causa que promueve esfuerzos de empresas en conjunto con sus clientes para apoyar causas sociales (Kotler & Lee, 2004).…”
Section: Antecendentesunclassified
“…Este Modelo Ecológico Conductual (BEM) inicia comprendiendo las motivaciones y los comportamientos de las personas dentro de su sistema social incluyendo a todos los actores relevantes inclusive la industria (Brennan et al, 2015), porque los comportamientos de las personas están dentro de un sistema social y se explican por las influencias bidireccionales o multidireccionales que van desde la capa social (macro-sistema: contexto político y sociocultural), a través de capas comunitarias y locales (meso-sistemas: influencias sociales o facilitadores y conexiones entre actores) y al individuo en su microsistema, exo-sistema y el meso-sistema, repercutiendo en factores que influyen tanto en el individuo como en las entidades del sistema, por lo que se requiere la cooperación de varios interesados para crear soluciones sostenibles a los problemas sociales (Brennan et al, 2016).…”
Section: Fundamento Teóricounclassified